The effects of nasal septum deviation on eye posterior segment finding (Annals of Medical Research, 2021)
Aim: Deviation of the nasal septum, which can cause upper respiratory tract obstruction and systemic hypoxia, may also affect the eye. The aim of this study was to detect changes in posterior segment parameters of the eye in patients with nasal septal deviation. Material and Methods: The study included 50 patients with nasal septal deviation, and a control group of 30 healthy subjects with no nasal septal deviation. Choroidal thickness, central macular thickness and retinal nerve fiber layer thickness were measured with Optical Coherence Tomography.Results: Choroidal thickness was significantly lower in patients with severe nasal septal deviation compared to the control group. (p=0.001) There is no statistically significant change in other measurements.Conclusion: The study results suggest that marked nasal septal deviation may lead to signiﬁcant hypoxia and sympathetic activation, resulting in deterioration of the choroidal blood ﬂow and consequent choroidal thickening.